What adults and adolescents are eating in rural South Asia (Webinar session 11) - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
Transforming Agrifood Systems in South Asia (TAFSSA), a CGIAR Initiative, hosted a webinar on ‘What are people eating in South Asia: Evidence from district assessment in Bangladesh, India and Nepal’, on June 6, 2024, from 4:00 pm to 5:00 pm IST. This is part of TAFSSA’s 2024 webinar series to highlight the research findings based on a comprehensive sub-national agrifood systems assessment conducted in early 2023 in rural areas of five districts across Bangladesh, India and Nepal.